In Vitro Packaging of UV Radiation-Damaged DNA from Bacteriophage T7 - Kuemmerle, Nancy B. (1977)
When DNA from bacteriophage T7 is irradiated with UV light, the efficiency with which this DNA can be packaged in vitro to form viable phage particles is reduced. A comparison between irradiated DNA packaged in vitro and irradiated intact phage particles shows almost identical survival as a function of UV dose when Escherichia coli wild type or polA or uvrA mutants are used as the host. Although uvrA mutants perform less host cell reactivation, the polA strains are identical with wild type in their ability to support the growth of irradiated T7 phage or irradiated T7 DNA packaged in vitro into complete phage. An examination of in vitro repair performed by extracts of T7-infected E.coli suggests that T7 DNA polymerase may substitute for E. coli DNA polymerase I in the resynthesis step of excision repair. Also tested was the ability of a similar in vitro repair system that used extracts from uninfected cells to restore biological activity of irradiated DNA. When T7 DNA damaged by UV irradiation was treated with an endonuclease from Micrococcus luteus that is specific for pyrimidine dimers and then was incubated with an extract of uninfected E. coli capable of removing pyrimidine dimers and restoring the DNA of its original (whole genome size) molecular weight, this DNA showed a higher packaging efficiency than untreated DNA, thus demonstrating that the in vitro repair system partially restored the biological activity of UV-damaged DNA.